2000
DOI: 10.1046/j.1570-7458.2000.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

A natural flightless mutation in the ladybird, Harmonia axyridis

Abstract: A homozygous flightless strain, obtained by selection from a laboratory population of Harmonia axyridis Pallas (Coleoptera, Coccinellidae), has been reared under controlled conditions since 1982 after sampling in China. The adults of this flightless strain have normal elytra and wings but drop almost vertically when they attempt to fly. The origin of this mutation, whether laboratory or natural, is discussed. As the mutation does not affect the fitness of the beetles, this flightless strain can be used in biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…A natural flightless strain of H. axyridis (Tourniaire et al, 2000) was maintained on E. kuehniella eggs as described by Schanderl et al (1988). For experiments, adults and immature stages were reared in Plexiglas cages at 23.5 ± 0.5°C, 75 ± 5% RH, and a 16:8 (L:D) photoperiod, and fed daily ad libitum, either with A. pisum adults or with E. kuehniella eggs.…”
Section: Insect Culturementioning
confidence: 99%
See 1 more Smart Citation
“…A natural flightless strain of H. axyridis (Tourniaire et al, 2000) was maintained on E. kuehniella eggs as described by Schanderl et al (1988). For experiments, adults and immature stages were reared in Plexiglas cages at 23.5 ± 0.5°C, 75 ± 5% RH, and a 16:8 (L:D) photoperiod, and fed daily ad libitum, either with A. pisum adults or with E. kuehniella eggs.…”
Section: Insect Culturementioning
confidence: 99%
“…To increase their efficiency in biological control, a natural flightless mutation was selected in a laboratory population of H. axyridis (Ferran et al, 1998;Tourniaire et al, 2000). We used this strain to conduct the research described in this study.…”
Section: Introductionmentioning
confidence: 99%
“…These factors can lead to reduced survival and reproductive characteristics of flightless ladybirds by inbreeding depression. The survival rate and fecundity of H. axyridis did not differ between adults of a flightless strain and those capable of flight (control strain) in the 15th generation after starting artificial selection (Tourniaire et al, 2000). However, with some biological control agents, depressed survival and reproductive characteristics have been observed in strains that have been colonized for a long time but not in recently colonized strains (Geden et al, 1992;De Clercq et al, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…Marples et al (1993) suggested that if ladybirds were poor flyers they would remain on a crop for longer and have potential in the long-term control of aphids. Flightless strains have been established from laboratory and field populations of the Coccinellids Harmonia axyridis (Pallas) (Ferran et al, 1998;Tourniaire et al, 2000;Seko et al, 2008), Adalia bipunctata (with a wingless morph) (L.) (Marples et al, 1993;Ueno et al, 2004;Lommen et al, 2005), and Rhyzobius litura (F.) (with a short-winged morph) (Hammond, 1985). Some of these strains are effective for augmentative biological control of aphids (Ferran et al, 1998;Weissenberger et al, 1999;Lommen et al, 2008;Seko et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation